Arahan Pencegahan dan Peningkatan Kualitas Permukiman Kumuh Kecamatan Binamu Kabupaten Jeneponto - Ameliya Magfirah; Syafri Syafri; Rusneni Ruslan (Journal of Urban Planning Studies, 2022)
. This study aims to analyze the causes of slums and determine the direction of prevention and improvement of the quality of slum settlements in the Biringjene Area, Binamu District, and Jeneponto Regency. This type of research is mixed-methods research. To analyze the factors that cause slums in the Biringjene area, Binamu District, and Jeneponto Regency, the Analytical Hierarchy Process analysis tool is used to formulate the direction of prevention and improvement quality improvement in the Biringjene area, qualitative descriptive analysis is used. Based on the results of the Analytical Hierarchy Process, the main conclusion of this study showed that the factors causing slums in the Biringjene Region, Binamu District, and Jeneponto Regency were socio-economic factors. This is due to the low income of the community, the unequal distribution of jobs, and the low level of education. The direction of prevention and quality improvement in the Biringjene Area, Binamu District, Jeneponto Regency is clarity through control, community empowerment, rejuvenation, and resettlement